Terahertz electromagnetic field propagation in human tissues: A study on communication capabilities; Nano Communication Networks; Vol. 10 - Piro G. Giuseppe; Bia P. Pietro; Boggia G. Gennaro; Karatelli D. Diego; Grieco L. A. Luigi Alfredo; Mescia L. Luciano (2016, 2016)
Title screen